MnO(2) prepared by hydrothermal method and electrochemical performance as anode for lithium-ion battery - Feng, Lili (Springer, 2014)
Two α-MnO(2) crystals with caddice-clew-like and urchin-like morphologies are prepared by the hydrothermal method, and their structure and electrochemical performance are characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), galvanostatic cell cycling, cyclic voltammetry, and electrochemical impedance spectroscopy (EIS). The morphology of the MnO(2) prepared under acidic condition is urchin-like, while the one prepared under neutral condition is caddice-clew-like. The identical crystalline phase of MnO(2) crystals is essential to evaluate the relationship between electrochemical performances and morphologies for lithium-ion battery application. In this study, urchin-like α-MnO(2) crystals with compact structure have better electrochemical performance due to the higher specific capacity and lower impedance. We find that the relationship between electrochemical performance and morphology is different when MnO(2) material used as electrochemical supercapacitor or as anode of lithium-ion battery. For lithium-ion battery application, urchin-like MnO(2) material has better electrochemical performance.